( | 2 | x | + | 4 | ÷ | 7 | × | x | ) | ÷ | ( | x | + | 10 | ) | = | 3 | ÷ | 2 |
Multiply both sides of the equation by: | ( | x | + | 10 | ) |
( | 2 | x | + | 4 | ÷ | 7 | × | x | ) | = | 3 | ÷ | 2 | × | ( | x | + | 10 | ) |
2 | x | + | 4 | ÷ | 7 | × | x | = | 3 | ÷ | 2 | × | ( | x | + | 10 | ) |
2 | x | + | 4 | ÷ | 7 | × | x | = | 3 | ÷ | 2 | × | x | + | 3 | ÷ | 2 | × | 10 |
2 | x | + | 4 7 | x | = | 3 2 | x | + | 15 |
18 7 | x | = | 3 2 | x | + | 15 |
18 7 | x | − | 3 2 | x | = | 15 |
15 14 | x | = | 15 |
x | = | 15 | ÷ | 15 14 |
= | 15 | × | 14 15 |
= | 1 | × | 14 |
x | = | 14 |